Carbon Starvation Can Induce Energy Deprivation and Loss of Fermentative Capacity in Saccharomyces cerevisiae - Thomsson, Elisabeth (American Society for Microbiology, 2003)
Seven different strains of Saccharomyces cerevisiae were tested for the ability to maintain their fermentative capacity during 24 h of carbon or nitrogen starvation. Starvation was imposed by transferring cells, exponentially growing in anaerobic batch cultures, to a defined growth medium lacking either a carbon or a nitrogen source. After 24 h of starvation, fermentative capacity was determined by addition of glucose and measurement of the resulting ethanol production rate. The results showed that 24 h of nitrogen starvation reduced the fermentative capacity by 70 to 95%, depending on the strain. Carbon starvation, on the other hand, provoked an almost complete loss of fermentative capacity in all of the strains tested. The absence of ethanol production following carbon starvation occurred even though the cells possessed a substantial glucose transport capacity. In fact, similar uptake capacities were recorded irrespective of whether the cells had been subjected to carbon or nitrogen starvation. Instead, the loss of fermentative capacity observed in carbon-starved cells was almost surely a result of energy deprivation. Carbon starvation drastically reduced the ATP content of the cells to values well below 0.1 μmol/g, while nitrogen-starved cells still contained approximately 6 μmol/g after 24 h of treatment. Addition of a small amount of glucose (0.1 g/liter at a cell density of 1.0 g/liter) at the initiation of starvation or use of stationary-phase instead of log-phase cells enabled the cells to preserve their fermentative capacity also during carbon starvation. The prerequisites for successful adaptation to starvation conditions are probably gradual nutrient depletion and access to energy during the adaptation period.